HASIL BIJI KACANG GUDE [Cajanus cajan (L.) Millsp] KULTIVAR MEGA DAN GALUR ICPL 84031 AKIBAT PEMULSAAN JERAMI PADI DAN PEMUPUKAN P PADA BERBAGAI JARAK TANAM YIELD OF PIGEON PEA [Cajanus cajan (L.) Millsp] MEGA CULTIVAR AND ICPL 84031 LINE AFFECTED BY PADDY STRAW MULCHING AND P FERTILIZER AT VARIOUS CROP SPACINGS - , Fathurrahman (Pembangunan Pedesaan, 2005)
A field experiment was conducted to study the effects of paddy straw mulching and P fertilizer on yield of two pigeon pea genotypes in Palu dry-land. The experiment was carried out in Mpanau, Palu district, Central Sulawesi. The experiment used randomized block design in factorial pattern consisted of four factors with three replications as follows: (1) two pigeon pea genotypes (Mega cultivar and ICPL 84031 line); (2) three levels of crop spacing (30 cm x 20 cm, 40 cm x 20 cm, and 50 cm x 20 cm); (3) four levels of paddy straw mulching (0, 2, 4, -1 -1 and 6 t ha ); (4) four levels of P fertilizer (0, 50, 100, and 150 kg ha ). Results of this experiment showed that ICPL 84031 line gave the maximum yield of seed -1 -1 (1,91 t ha ) obtained from optimum mulching level of 4,83 t ha and optimum P -1 rate of 125,29 kg ha at 30 cm x 20 cm crop spacing. Mega cultivar gave the -1 maximum yield of seed (1,11 t ha ) obtained from optimum mulching level of 4,13 t -1 -1 ha and optimum P rate of 148,13 kg ha at 30 cm x 20 cm crop spacing.